Effect of UV-B radiation on UV absorbing compounds and pigments of moss and lichen of Schirmacher oasis region, East Antarctica - Singh, J.; Gautam, S.; Bhushan pant, A. (Cellular and Molecular Biology, 2012)
The survival of Antarctic flora under ozone depletion depends on their ability to acclimate against increasing UV-B radiation by employing photo protective mechanisms either by avoiding or repairing UV-B damage. A fifteen days experiment was designed to study moss (Bryum argenteum) and lichen (Umbilicaria aprina) under natural UV-B exposure and under UV filter frames at the Maitri region of Schirmacher oasis, East Antarctica. Changes in UV absorbing compounds, phenolics, carotenoids and chlorophyll content were studied for continuous fifteen days and significant changes were observed in the UV exposed plants of B. argenteum and U. aprina. The change in the UV absorbing compounds was more significant in B. argenteum (P<0.0001) than U. aprina (P<0.0002). The change in phenolic contents and total carotenoid content was significant (P<0.0001) in both B. argenteum and lichen U. aprina indicating that the increase in UV absorbing compounds, phenolic contents and total carotenoid content act as a protective mechanism against the deleterious effect of UV-B radiations.